KEKERASAN DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER - Mardiansyah, Dedy; Fitriyah, Lailatul; Lestari, Silvya Anggun; Lismawati, Deli (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research discusses the issue of violence contained in the novel Bumi Kunci by Pramoedya Ananta Toer. This research was conducted using a qualitative descriptive method. The data is in the form of sentence quotations and is collected using the note-taking technique. Next, the collected data was analyzed using interactive techniques that emphasize the principle of continuity in the data collection and analysis process. Through Fairclough's critical discourse analysis model, this research identifies two problems of violence raised in the story, namely physical and psychological violence. The results of this research show that violence has a big impact on the survival of each individual, the impact is even long-term. This novel also provides a picture of life in the Dutch East Indies era and reminds us of the importance of overcoming violence against indigenous groups, weak groups and gender which is still a problem today throughout the world.